Transitory legality: the health implication of ending DACA - Mallet-Garcia, M; Garcia Bedolla, L (University of California, Berkeley, 2019)
This paper examines the effects of the rescission announcement of the DACA program on the health outcomes of Latino DACA recipients in California. Research shows that undocumented immigrants face poorer health outcomes than their documented counterparts and U.S. citizens, and that being offered legal status (e.g. DACA) considerably improves their health outcomes. Even though studies have examined the impact of shifting legal status on incorporation, to our knowledge no studies have considered the effects of announcing the rescission of the DACA program on its recipients. However, this is important because it may have implications on their health outcomes. This study addresses this gap by using in-depth interviews with 43 Latino DACA recipients living in the California San Francisco Bay Area in 2017 and 2018. Our findings suggest that rescission announcement of DACA has led to worsening health outcomes for DACA recipients. Specifically, we find that it created what we call a state of transitory legality among the 1.5 generation, which causes DACA recipients to experience health outcomes that are worse than those before DACA. Our results are important in the field of sociology, public policy and heath care because they show the negative effects of reversing inclusionary immigration policies on the health outcomes of undocumented Latino immigrants.